Erenumab‐Induced Severe Nausea Leading to Smoking Cessation: A Retrospective Case Series. Issue 10 (17th November 2020) - Mathew, Paul G.; Krivitski, David; Sharon, Roni
Abstract : Objective: Erenumab is a novel treatment modality with a relatively benign and safe side effect profile, currently approved for the prevention of migraine headache. We present 3 cases with chronic migraine who are cigarette smokers were prescribed erenumab, and developed an intense smoking‐induced nausea which eventually led to smoking cessation. Methods: A multicenter retrospective review of 3 cases with cigarette smoking, one of whom was also smoking marijuana, suffering from chronic migraine resistant to multiple preventive therapies was studied. All were prescribed monthly injections of erenumab 70 mg. Response in terms of headache frequency and intensity and smoking habits was obtained through medical record review. Results: Out of 3 patients, 2 reported reduced headache frequency and intensity. All patients developed severe nausea while smoking cigarettes after their first dose of erenumab, leading to smoking cessation. One patient co‐smoked marijuana, which did not result in nausea after being treated. Conclusion: To the best of our knowledge, this is the first report of severe nausea secondary to erenumab administration and smoking cigarettes, which finally resulted in complete cigarette smoking cessation. As such, further study is indicated on the benefit of erenumab and other calcitonin gene‐related peptide antagonists in migraineurs who smoke to promote smoking cessation.